Andrew Asibong. Marie NDiaye: Blankness and Recognition. Liverpool: Liverpool UP, 2013. - Katarzyna Peric (Studies in 20th & 21st Century Literature, 2016)
Review of Andrew Asibong. Marie NDiaye: Blankness and Recognition. Liverpool: Liverpool UP, 2013.
Keywords: Marie NDiaye